Pengembangan Program Penghafalan Al- Qur’an Surat-Surat Pendek Pada Anak-Anak di Kelurahan Belawan Sicanang - Khairunnisa Mifta Ababil (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to develop an effective and engaging program for memorizing short Surahs of the Qur’an among children in Belawan Sicanang Village. The background of this research stems from the low interest and ability of children to memorize the Qur’an, particularly in coastal communities with limited access to religious education facilities. This study employs a qualitative approach using a Research and Development (RD) model, which includes the stages of needs analysis, program design, implementation, and evaluation. Data were collected through observation, interviews with Qur’an teachers, parents, and children, as well as documentation of learning activities. The results show that the memorization program developed through play-based learning, storytelling, and the use of audio-visual media effectively increased children’s motivation and memorization ability. Moreover, family and teacher support played a vital role in the program’s success. Therefore, this developed program can serve as a relevant and contextual model for Qur’an memorization learning in coastal communities, particularly in Belawan Sicanang.